Elastically Graded Titanium Alloy Produced by Mechanical Surface Deformation - Delannoy, Stéphanie; Baïz, Sarah; Laheurte, Pascal; Jordan, Laurence; Prima, Frédéric (Frontiers in Materials, 2021)
The objective of this study was to develop a thermo-mechanical strategy to create a radial elasticity gradient in a β metastable Ti-Nb-Zr alloy, and to characterize it in terms of microstructural and mechanical properties. A first investigation was conducted on thin samples of Ti-20Nb-6Zr (at.%) submitted to various thermo-mechanical treatments. Microstructure-properties relationships and elastic variability of this alloy were determined performing uniaxial tensile tests, X-ray diffraction and scanning and transmission electron microscopies. Based on these preliminary results, mechanical deformation was identified as a potential way to lower the elastic modulus of the alloy. In order to create elastically graded pieces, shot-peening was therefore carried out on thicker samples to engender surface deformation. In this second part of the work, local mechanical properties were evaluated by instrumented micro-indentation. Experimental observations demonstrated that shot-peening enabled to locally induce martensitic transformation on surface, and a decrease in indentation elastic modulus from 85 to 65GPa over 400µm was highlighted. Surface deformation proved to be an efficient way of creating an elasticity gradient in β metastable titanium alloys. This combination of material and process could be suitable to produce dental implants with mechanically enhanced biocompatibility.